The road to Paris: Stress testing the transition towards a net-zero economy. The energy transition through the lens of the second ECB economy-wide climate stress test - Tina Emambakhsh; Maximilian Fuchs; Simon Kördel; Charalampos Kouratzoglou; Chiara Lelli; Riccardo Pizzeghello; Carmelo Salleo; Martina Spaggiari (European Central Bank (ECB), 2023)
The transition to a carbon-neutral economy is necessary to limit the negative impact of climate change and has become one of the world's most urgent priorities. This paper assesses the impact of three potential transition pathways, differing in the timing and level of ambition of emission reductions, and quantifies the associated investment needs, economic costs and financial risks for corporates, households and financial institutions in the euro area. Building on the first ECB top-down, economy-wide climate stress test, this paper contributes to the field of climate stress testing by introducing three key innovations. First, the design of three short-term transition scenarios that combine the transition paths developed by the Network for Greening the Financial System (NGFS) with macroeconomic projections that account for the latest energy-related developments. Second, the introduction of granular sectoral dynamics and energy-specific considerations by country relevant to transition risk. Finally, this paper provides a comprehensive analysis of the impact of transition risk on the euro area private sector and on the financial system, using a granular dataset that combines climate, energy-related and financial information for millions of firms within the euro area credit register and securities database, and country-level data on households. By comparing different transition scenarios, the results of the exercise show that acting immediately and decisively would provide significant benefits for the euro area economy and financial system, not only by maintaining the optimal net-zero emissions path (and therefore limiting the physical impact of climate change), but also by limiting financial risk. An accelerated transition to a carbon-neutral economy would be helpful to contain risks for financial institutions and would not generate financial stability concerns for the euro area, provided that firms and households could finance their green investments in an orderly manner. However, the heterogeneous results across economic sectors and banks suggest that more careful monitoring of certain entities and subsets of credit exposures will be required during the transition process.
Keywords: C53; C55; G21; Q47; Q54; 330; climate stress test; transition risk; climate scenarios; energy